Stability of platoon of adaptive cruise control vehicles with time delay. Issue 9 (10th October 2019) - Hu, San Gen; Wen, Hui Ying; Xu, Lunhui; Fu, Hui
Abstract: In this paper, the stability criteria of a platoon of adaptive cruise control (ACC) vehicles with actuator lag and senor delay are derived, and their impact on ACC vehicles stability is analyzed and tested. The results show that compared to the ideal ACC model with zero delays, both sensor delay and actuator lag deteriorate the dynamic stability of vehicles and platoons; they, however, have negligible impact on the static performance. Comparatively, the negative effect from communication delay is larger than that from actuator lag. In order to minimize the impacts of the two types of delays, a new ACC model is proposed. Then, the optimal control parameters of the proposed ACC system are designed based on a proportional-derivative controller from the perspective of the homogeneous and heterogeneous string stability. The results provide a feasible design to the proportional-derivative controller of ACC. Finally, the sensitivity analysis of ACC system is conducted.